2012
DOI: 10.1890/es12-00048.1
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for a graph‐theoretic implementation of structural equation modeling

Abstract: Abstract. Structural equation modeling (SEM) is increasingly being chosen by researchers as a framework for gaining scientific insights from the quantitative analyses of data. New ideas and methods emerging from the study of causality, influences from the field of graphical modeling, and advances in statistics are expanding the rigor, capability, and even purpose of SEM. Guidelines for implementing the expanded capabilities of SEM are currently lacking. In this paper we describe new developments in SEM that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
454
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 478 publications
(458 citation statements)
references
References 92 publications
(116 reference statements)
0
454
0
4
Order By: Relevance
“…Furthermore, there has been an infusion of new ideas into quantitative modeling, such as the discovery that it is necessary to formalize causal reasoning for artificial intelligence systems [55]. These ideas are now being incorporated into SEM, providing a stronger foundation for developing and testing multivariate models [67].…”
Section: Box 3 From General Theories To Quantitative Modelsmentioning
confidence: 99%
“…Furthermore, there has been an infusion of new ideas into quantitative modeling, such as the discovery that it is necessary to formalize causal reasoning for artificial intelligence systems [55]. These ideas are now being incorporated into SEM, providing a stronger foundation for developing and testing multivariate models [67].…”
Section: Box 3 From General Theories To Quantitative Modelsmentioning
confidence: 99%
“…'mediating' effects (defined in Grace et al, 2012), were examined with mediation tests (d-separation tests, Shipley, 2009;Clough, 2012). We first considered which abiotic variable (serpentine soils or elevation) was significantly related to each biotic condition (overstorey shading, litter, understorey cover, mycorrhizal or septate fungal colonization) and whether these biotic conditions were significantly associated with plant variables (presence, abundance or reproduction).…”
Section: Discussionmentioning
confidence: 99%
“…This method is suitable to examine causal relationships of direct and indirect effects of predictor on response variables [76]. In addition, SEM allows for the estimation of composite variables not directly measured in the study (also called latent variables), by including two or more observed variables [77]. For each species, we fitted models with significant predictor variables and with importance values greater than 0.70 according to the GLMMs and variables directed linked to the hypothesis of this study, namely, sea surface temperature, chlorophyll-a concentrations, wave height and river outflow.…”
Section: Methodsmentioning
confidence: 99%